2011
DOI: 10.1016/j.psychres.2010.10.034
|View full text |Cite
|
Sign up to set email alerts
|

Protective factors for posttraumatic stress disorder symptoms in a prospective study of police officers

Abstract: Although police officers are frequently exposed to potentially traumatic incidents, only a minority will develop chronic Posttraumatic Stress Disorder (PTSD). Identifying and understanding protective factors could inform the development of preventive interventions; however, few studies have examined this. In the present prospective study, 233 police officers were assessed during academy training and again following two years of police service. Caucasian race, less previous trauma exposure, and less critical in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
67
1
12

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 89 publications
(84 citation statements)
references
References 49 publications
4
67
1
12
Order By: Relevance
“…Although the amount of combat experienced by the two age brackets was not significantly different, it appears that those ages 26-35 were at less risk of worsening than those 25 and under. Our finding that Black race was associated with general mental health worsening is somewhat consistent with a finding of Yuan and colleagues [47] who observed, in a prospective study, that Caucasian race was predictive of lower PTSD symptoms in a prospective study of police officers. In addition, being of minority race was consistently mentioned as an initiation risk for PTSD in Brewin's meta-analysis [46].…”
Section: Discussionsupporting
confidence: 92%
“…Although the amount of combat experienced by the two age brackets was not significantly different, it appears that those ages 26-35 were at less risk of worsening than those 25 and under. Our finding that Black race was associated with general mental health worsening is somewhat consistent with a finding of Yuan and colleagues [47] who observed, in a prospective study, that Caucasian race was predictive of lower PTSD symptoms in a prospective study of police officers. In addition, being of minority race was consistently mentioned as an initiation risk for PTSD in Brewin's meta-analysis [46].…”
Section: Discussionsupporting
confidence: 92%
“…These findings are consistent with other research on child welfare workers which has found no relationship between emotional and professional support and trauma symptoms (Horwitz, 2006). It is inconsistent with research outside of the child welfare profession, which has found that among those suffering a workplace trauma, higher rates of peer, supervisor, and non-work support have been negatively related to PTSD (Matthews, 2006;Stephens & Long, 1999;Wilson, Poole, & Trew, 1997;Yuan et al, 2011). An area for future research is whether the culture of child welfare work prevents support from being more helpful.…”
Section: Support For Workers Experiencing Maltreatment Fatalitiessupporting
confidence: 66%
“…For example, low self-worth has been strongly related to high levels of posttraumatic stress symptoms across different types of traumatic experiences (e.g., [74,78,79,81,82]). Low levels of assumption of benevolence of the world or other people have been related to greater posttraumatic stress symptoms in the studies (e.g., [74,[77][78][79][80]82] ).…”
Section: Introductionmentioning
confidence: 84%
“…The WAS has been widely used to explain the psychological reactions to traumatic events such as combat-related stress [74], torture [75], and natural disaster [76]. One recent study [77] found that police academy cadets with a greater sense of self-worth and stronger beliefs about the benevolence of the world experienced fewer symptoms of PTSD after two years of service, suggesting that an of icer's world assumptions can act as a buffer against the deleterious effects of exposure to trauma. Many studies have found that people with posttraumatic stress symptoms have more negative world assumptions than people without such reactions (e.g., [78][79][80]).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation